Assessing Executive Dysfunction in Neurodegenerative Disorders: A Critical Review of Brief Neuropsychological Tools - Moreira, Helena S.; Costa, Ana S.; Castro, São L.; Lima, César F.; Vicente, Selene G. (Frontiers in Aging Neuroscience, 2017)
Executive function (EF) has been defined as a multifaceted construct that involves a variety of high-level cognitive abilities such as planning, working memory, mental flexibility and inhibition. Being able to identify deficits in EF is important for the diagnosis and monitoring of several neurodegenerative disorders, and thus their assessment is a topic of much debate. In particular, there has been a growing interest in the development of neuropsychological screening tools that can potentially provide a reliable quick measure of EF. In this review, we critically discuss the four screening tools of EF currently available in the literature: Executive Interview-25 (EXIT 25), Frontal Assessment Battery (FAB), INECO Frontal Screening (IFS), and FRONTIER Executive Screen (FES). We first describe their features, and then evaluate their psychometric properties, the existing evidence on their neural correlates, and the empirical work that has been conducted in clinical populations. We conclude that the four screening tools generally present appropriate psychometric properties, and are sensitive to impairments in EF in several neurodegenerative conditions. However, more research will be needed mostly with respect to normative data and neural correlates, and to determine the extent to which these tools add specific information to the one provided by global cognition screening tests. More research directly comparing the available tools with each other will also be important to establish in which conditions each of them can be most useful.